Participação popular e Plano Diretor Municipal (PDM) : estudo de caso de Cariacica, Região metropolitana de Vitória, ES - Fernandes, Flávio Palhano (2010)
The inclusion of popular participation in planning and managing of the municipal urban space in the country is a recent conquest, which is a result of the struggle of many social activisms to improve the Urban Reform. It is under this context that this study focuses on the process of popular participation in the working out of Municipal Master Plan (Plano Diretor Municipal - PDM), a requirement from the federal law 10.257/2001, known as the City Statute. The implication of this work will be done through a case study of the development of Cariacica´s PDM. Cariacica is a city with approximately 350,000 inhabitants, it is part of the Região Metropolitana of Grande Vitória in Espírito Santo. For the accomplishment of this work we adopted as methodology some indicators of qualitative performance proposed by SOUZA (2006), to analyze the opening degree to the participation of the resident population of Cariacica throughout the drafting of the PDM and the consistency of such participation. Through interviews and study of documents/reports we made a rebuilding the process of inserting the population over the development of the PDM since the initial discussion until the debate in open court, and subsequent referral to the City Council. As result, overall, the analysis from the qualitative indicators showed low, and sometimes moderate consistency and ambition level of opening to the participation of Cariacicas´s resident population during the development of PDM, which lead us to question the real popular participation, and its profits, in the master plans made in the country. If on one hand the City Statute brought for the debate the importance of popular participation in the development of PDM, the case of Cariacica demonstrated that there is still an important part of the way to go in order to create a participatory space effectively to make a territorial planning that enables gains in favor of a more fair city. In the end, we intend that this study contributes to the improvement of the future routines of popular participation in the city, considering the potential of this participation beyond its limitations.